Qualche appunto per l’edizione e il commento di A tanto caro sangue di Giovanni Raboni* - Zucco, Rodolfo (Cuadernos de Filología Italiana, 2006)
The edition of Giovanni Raboni’s poetical works causes, before all, the problem of the relation between the auto-anthology A tanto caro sangue (1988) and the preceding books. The author and the editor have deemed it necessary to present integrally A tanto caro sangue at the side of Le case della Vetra, Cadenza d’inganno, Nel grave sogno and Canzonette mortali, respecting the original conception of A tanto caro sangue as an autonomous book, the result of the author’s reflection about his own work on the ground of those «thematic (or tonal, or emotional) prevalences» the structure of this book is due to. The essay proposes the notes of introduction to the six parts of A tanto caro sangue and a commentary to the sequence Scongiuri vespertini.